PENGEMBANGAN MEDIA LEMBAKOTA (LEMBAR BALIK KOSAKATA) MATERI MENULIS PERMULAAN SISWA KELAS I SDN BURENGAN 1 - Arista Berliana Putri, Cindy; Saidah, Karimatus; Sri Mujiwati, Endang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The writing ability of the first grade students of SDN Burengan 1 is still in the low category for 14 out of 23 students, with scores below the KKM 75 and the minimal use of media innovation, especially in Indonesian, is still low. This study aims to develop the Lembakota (Vocabulary Flip Chart) media and to describe its validity, practicality, and effectiveness in improving beginning writing skills of first-grade students at SDN Burengan 1, Kediri City. The research employed a Research and Development (R&D) method using the ADDIE model. The trial subjects consisted of 6 students in a limited trial and 17 students in a field trial. Primary data were collected through observation, interviews, questionnaires, and tests, and were analyzed quantitatively and qualitatively to evaluate the feasibility of the developed media. The results show that Lembakota is feasible to use, with a validity percentage of 90.43% categorized as very valid. In terms of practicality, the media obtained a score of 100% based on the teacher response questionnaire and 90% based on the student response questionnaire, indicating that it is very practical. In terms of effectiveness, the field trial involving 17 students achieved 100% classical mastery. Thus, Lembakota can be declared very effective in improving beginning writing skills of first-grade elementary school students.